2020
DOI: 10.21873/invivo.12085
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Radiological Assessment After Preservation Rhinoplasty – A Clinical Study

Abstract: Background/Aim: We hypothesized that improved functional outcome after preservation rhinoplasty can be validated by radiological analyses. Patients and Methods: In this retrospective study, five patients were included. Radiological assessment was evaluated by cone-beam computed tomography. Patient satisfaction regarding nasal function was evaluated by a Likert scale from 0 to 10 (0=poor result; 10=very satisfied). Results: After a mean follow-up of 5±1 months (range=4-6 months), significantly improved function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Sample sizes ranged between 5 and 136 patients. INV angle readings were obtained by CT for 428 patients (62.5%) in 12 studies, 4 , 8 , 18 , 20 , 22 , 24 26 , 29 – 33 and endoscopy was used for 256 patients (37.5%) in 6 studies. 3 , 17 , 21 , 24 , 26 , 32 Studies included patients from seven ethnicities, including 160 Caucasians (26.4%), 4 , 18 , 21 , 24 , 25 , 28 31 99 Egyptians (16.3%), 8 , 26 30 Mexican-Hispanics (5.0%), 3 46 Asians (7.6%), 20 , 25 28 Turkish (4.6%), 17 75 Indians (12.4%), 32 and 136 Koreans (22.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged between 5 and 136 patients. INV angle readings were obtained by CT for 428 patients (62.5%) in 12 studies, 4 , 8 , 18 , 20 , 22 , 24 26 , 29 – 33 and endoscopy was used for 256 patients (37.5%) in 6 studies. 3 , 17 , 21 , 24 , 26 , 32 Studies included patients from seven ethnicities, including 160 Caucasians (26.4%), 4 , 18 , 21 , 24 , 25 , 28 31 99 Egyptians (16.3%), 8 , 26 30 Mexican-Hispanics (5.0%), 3 46 Asians (7.6%), 20 , 25 28 Turkish (4.6%), 17 75 Indians (12.4%), 32 and 136 Koreans (22.4%).…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of the nasal appearance has been shown by many authors to be associated with a dramatic improvement in the functional outcome. 17,18 The ability to avoid skin undermining eliminates the requirement for fascia grafts and leads to a fine, smooth appearance, faster operation, with less edema; subsequently, the dorsal aesthetic line will be more preserved, the risk of long-term thinning will be decreased, and also the risk of dorsal deformity will be decreased. No skin undermining A high subdorsal septal strip is removed, and osteotomies are performed with an osteotome, adopting an external approach to release the osteocartilaginous vault from the midface.…”
Section: Discussionmentioning
confidence: 99%
“…Our article has limitations: There is a lack of objective measurements such as rhinomanometry and validated subjective patient reported outcome measures. Nevertheless, it has just recently been reported that a high patient satisfaction after PR can be achieved, as evaluated by the ROE, which goes in line with aesthetics and function [41][42][43]. Lastly, further studies are needed by using also the septal extracorporeal reconstruction technique, even endonasally together with dorsum PR [4].…”
Section: Discussionmentioning
confidence: 99%